Five new species of chirostylid crustaceans (Crustacea: Decapoda: Anomura: Chirostylidae) from Taiwan - Baba, Keiji; Lin, Chia-Wei (Zootaxa, 2008)
Five new species of chirostylid crustaceans from Taiwan are described. Eumunida chani sp. nov. is characterized by the absence of a pad of densely-packed setae on the pereopod 1, the anterior branchial margin bearing two spines, and the carpus of first pereopod with only two spines. Uroptychus anacaena sp. nov. and U. anatonus sp. nov. are similar but separated from each other by the shape of sternite 4 and relative length of the antennal scale. These species closely resemble U. maori Borradaile, 1916 and U. brucei Baba, 1986, but lack a ventral subterminal spine on the ischium of pereopod 1. Uroptychus orientalis sp. nov. is separated from U. occidentalis Faxon, 1893 by the shorter antennal scale and P2–4 dactyli with ultimate and penultimate spines subequal in size. Uroptychus singularis sp. nov. is distinguished from U. australis (Henderson, 1885) by the single, unpaired terminal spine on the flexor margin of pereopods 2–4.